2021
DOI: 10.1371/journal.pone.0245593
|View full text |Cite
|
Sign up to set email alerts
|

Polysubstance use among adolescents in Malaysia: Findings from the National Health and Morbidity Survey 2017

Abstract: Background Polysubstance use is defined as the use of more than one non-prescribed licit or illicit substance either concurrently or simultaneously. This study aimed to determine the prevalence of single substance users and polysubstance users and 'their associated factors among adolescents in Malaysia. Methods This study was a secondary data analysis from the National Health and Morbidity Survey (NHMS) 2017, a cross-sectional survey conducted among Malaysian school-going adolescents aged 13 to 17. The NHMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
2
17
2
2
Order By: Relevance
“…The interaction of drug use and ethnicity shows a greater effect for current e-cigarette use among non-current drug users. In contrast to our findings, local studies have reported that the use of substances was less likely to cluster in Malay compared to non-Malay adolescents [ 46 , 53 ]. With the smaller effect of ethnicity differences among current drug users, further study is needed to explore the nature of drug influence in Malay and non-Malay adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…The interaction of drug use and ethnicity shows a greater effect for current e-cigarette use among non-current drug users. In contrast to our findings, local studies have reported that the use of substances was less likely to cluster in Malay compared to non-Malay adolescents [ 46 , 53 ]. With the smaller effect of ethnicity differences among current drug users, further study is needed to explore the nature of drug influence in Malay and non-Malay adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…During adolescence, the developmental changes experienced by an individual are marked by emotional instability, which can interfere with positive decision-making [ 8 ]. Thus, adolescence is a period of vulnerability for the development of risky mental health behaviors [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experts argue that there may be a positive relationship between physical activity and brain health in adolescents, which involves both cognitive function and mental health [ 14 ]. Additionally, the use of licit or illicit psychoactive substances is associated with depression in adolescents [ 9 , 15 ]. In adolescence, episodes of rebellion and dangerous habits such as alcohol drinking and drug use may start to develop, especially among adolescents who lack the support of family and friends [ 9 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly-substance use has also been linked with risk behaviours other than substance use (e.g., risky sexual behaviour, gambling) and negative health outcomes above and beyond using each substance in isolation, including poor mental health and mental ill-health [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Of note, poly-substance use has been associated with elevated symptoms of depression and anxiety among adolescents aged 11 to 18 in cross-sectional research [ 5 , 21 , 22 , 23 , 24 ], although previous longitudinal research has identified mixed results. A large US study found no associations between poly-substance use and depressive symptoms after controlling for other variables [ 9 ].…”
Section: Introductionmentioning
confidence: 99%